Policy Implementation: Lessons from the Chilean Policy on Public Management Modernization - Olavarria-Gambi, M (Faculty of Social Sciences, 2017)
This paper analyses the implementation of public management modernization policy between 1990 and 2013, applying the taxonomy by Hasenfeld and Brock (1991). Information analysed in this study comes from 67 interviews with actors who have played key roles in the implementation of modernization initiatives, as well as from official documents, and academic literature. The findings of the study suggest that taxonomy is useful in characterizing the organizational and inter-organizational behavioural patterns that influence policy implementation; also, that the prevalent driving forces help to understand the dynamic of implementation and what capacities, abilities and strategies are required to put into practice a concrete public policy, which appear to be linked to the context in which implementation takes place.